(3aJGhi hCSFdI hQOJ Ydi GdeDda aj eSGFd aj Gdhba hZjQgG hELGHGJg YdjgGs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s ((3GdeOQSI GdYGOdjI(B_ (3OeTb s)
(3ChdgG (B:s
(3eSFdI hba Ydi HOQ GdOjf Hf YSGcQ HEbQGQI hgh ai jOg Ke Ydi ChdGOg s
(3BNQgG (B:s
(3hMUd dg eG bdfGg agh Cced hEf MUd dg NdGa Pdc addYHGO hGddg CYde s
(3jHOh Cf GdChQGb ajgG EVWQGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1223s
Keywords: (3Gdabg GdESdGejs